Depiction of the story of Vijay Seth and Vijay Sethani - Temples of India Project Team (Jio Institute, 2024)
Seen here is the story of Vijay Seth and Vijay Sethani, a couple who maintained the vow of celibacy throughout their life. The painting, on the ceiling of the mandapa (pillared hall) of the Bhandasar Temple, depicts a grandiose haveli with an enclosure where the couple resides. The painting has an inscription that reads, ‘Sethajidas Vijayseth Sethani ko Parna karata hai’.